Effect of Microbial Biopolymers on Mechanical Properties of Bauxite Residue - Bonal N.S.; Prasad A.; Verma A.K. (My University, 2025)
Natural polymer (biopolymer) treatment of engineered soil/waste is recognized as an environmentally-friendly sustainable method. This paper presents the findings in the improvement of strength characteristics of bauxite residue (red mud tailing) using two microbial biopolymers, xanthan (XG) and guar gum (GG), used individually and also together as a composite. A set of laboratory tests namely compaction test, sieve and hydrometer analysis, Atterberg limits, unconsolidated undrained triaxial (UU) test, unconfined compression (qu) test, chemical analysis, X-ray diffraction (XRD) and scanning electron microscopy (SEM) have been performed on biopolymer stabilized specimens at varying biopolymer concentration and curing period. The results showed that qu increases polynomially with the increase in biopolymer content (P) and curing period (t). Also, when compared with the conventional method, qu at 0.5% XG was similar to 10% cement stabilized bauxite residue at 28 days curing period. The influence of a composite biopolymer on the strengthening behaviour of bauxite residue is also observed due to the additional ability to create a cross-linking network. XRD and SEM micrographs have also confirmed that bauxite residue particles are linked through the biopolymer, resulting in improved shear resistance. Finally, considering environmental perspectives, the economic feasibility of biopolymer treatment is also examined in comparison to cement and found that the biopolymer usage is an excellent substitute to the conventional engineered materials (cement) for soil/waste treatment. © 2021, Korean Society of Civil Engineers.